85.0k views
23 votes
2x - y + 3z = -6
-x + 2y - 3z = 12
y + 5z = -6

1 Answer

1 vote

Answer:

Solving the system of equations we get:

x=2, y=4, z=-2

Explanation:

We need to solve the system of equations


2x - y + 3z = -6\\-x + 2y - 3z = 12\\y + 5z = -6

Let:


2x - y + 3z = -6--eq(1)\\-x + 2y - 3z = 12--eq(2)\\y + 5z = -6--eq(3)

First we find value of y from equation 3


y+5z=-6\\y=-6-5z

Put value of y in equation 1


2x - y + 3z = -6\\2x-(-6-5z)+3z=-6\\2x+6+5z+3z=-6\\2x+8z=-6-6\\2x+8z=-12---eq(4)

Now, put value of y in equation 2


-x + 2y - 3z = 12\\-x+2(-6-5z)-3z=12\\-x-12-10z-3z=12\\-x-13z=12+12\\-x-13z=24--eq(5)

Multiply equation 5 with 2 and add both equations 4 and 5


2x+8z=-12\\-2x-26z=48\\--------\\-18z=36\\z=(36)/(-18)\\z=-2

So, we get z=-2

Now put value of z in equation 3


y+5z=-6\\y+5(-2)=-6\\y-10=-6\\y=-6+10\\y=4

So, we get y=4

Now, put value of y=4, and z=-2 in equation 1


2x-y+3z=-6\\2x-4+3(-2)=-6\\2x-4-6=-6\\2x-10=-6\\2x=-6+10\\2x=4\\x=(4)/(2)\\x=2

So, solving the system of equations we get:

x=2, y=4, z=-2

User Celita
by
4.2k points